Identification of Factors Influencing the Presence of Fecal Coliforms in Densely Populated Areas with Centralized Wastewater Treatment Systems - Syafira Bunga Az Zahra; Ni Nyoman Nepi Marleni; Budi Kamulyan; Hendra Dewata (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Tegal Panggung is a high population density sub-district of 26,326 inhabitants/km2. Most residents utilize wells to meet their water demands, but fecal coliform bacteria were found in several wells at Tegal Panggung. This type of contamination source is typically from on-site wastewater treatments. However, wastewater from Tegal Panggung is treated at a centralized wastewater treatment plant. This study is aimed at identifying the factors leading to the presence of fecal coliform bacteria in Tegal Panggung. Methods: Factors reviewed in this study were the amount of waste, drainage, cattle pens, toilets, types of wells, and building density. Statistical methods and GIS were applied to determine the influence of the factors on the presence of fecal coliform and to map its distribution along with potential sources of pollution. The number of wells tested was 32, with a research period from September to October 2021. The statistical methods used are the Kolmogorov-Smirnov Normality Test, the Spearman Correlation Test, and the spatial analysis method, which was carried out using QGIS. The statistical tests were conducted to determine the correlation value between fecal coliform and pollutant. Results and Discussion: The study showed that only 40.62% met the standard requirements when there should be no fecal coliform contents in well water. Conclusion: Based on the Spearman Correlation Test, it can be deduced that the factors affecting the presence of fecal coliform within 10 meters radius are garbage and of 30 meters radius are toilets and building density.